Dinamika Struktur Modal di Sektor Konsumen Non-Siklus Indonesia: Pengaruh Profitabilitas, Struktur Aset dan Ukuran Perusahaan - Haliza, Vivi Dwi; Tubastuvi, Naelati; Rahmawati, Ika Yustina; Kharismasyah, Alfato Yusnar (Universitas Airlangga, 2025)
Capital structure is one of the important aspects in corporate finance since it displays the business’s policy in choosing financing sources. This study examines how capital structure is impacted by profitability, asset structure, and company size, specifically emphasizing businesses in the consumer non-cyclicals sector. The study uses quantitative analysis, the population consists of 132 companies in the consumer non-cyclicals category that were listed on the IDX between 2020-2023, with sampling using a purposive sampling technique, which resulted in 47 companies. This analysis uses multiple linear regression with SPSS 25. Consequently, capital structure is significantly impacted negatively by profitability, whereas asset structure and firm size are significantly impacted favorably. This result is consistent with the trade-off theory and pecking order theories, which hold that profitable businesses typically use internal funding, while asset structure and company size become collateral to obtain external funding. Companies are encouraged to increase their revenue and income streams. For Investors, before extending credit or making investment decisions, lenders and potential investors should carefully assess the company's profitability ratio, asset configuration, and overall size.